Prinsip Pelaksanaan Pengelolaan Kelas Dalam Pembelajaran Bahasa Indonesia: Penelitian - Vinkan Pramesti Y. Tilome; Sayama Malabar; Puspita Dian Agustin (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2025)
This study aims to describe the planning of classroom management in Indonesian language learning seen from the teaching module, the implementation of classroom management in Indonesian language learning seen from the implementation of learning, supervision of classroom management in Indonesian language learning, inhibiting factors, and solutions to overcome inhibiting factors in classroom management in Indonesian language learning. Using a descriptive research method with a qualitative research type. The results of this study indicate that the planning of classroom management in Indonesian language learning seen from the teaching module is very good, because in the module there are principles of classroom management in the form of warmth and enthusiasm, challenges, variations, flexibility, instilling self-discipline and emphasizing positive things. In the implementation of classroom management carried out by teachers in Indonesian language learning, the implementation of learning is also very good, because the implementation of learning Indonesian language teachers apply the 6 principles of classroom management. However, in the supervision of classroom management carried out by teachers in Indonesian language learning, there is 1 classroom management plan that is not carried out by teachers, namely evaluation and feedback when ending learning.